PRICE TRANSMISSION BETWEEN U.S. GRAIN AND KOREAN IMPORT GRAIN - Renee Kim (University of Manitoba Winnipeg, Canada, 2006)
This study examines the price transmission between U.S. farm level grain prices and Korean imported grain prices. Price transmission results for corn, soybeans, and wheat indicate that the policy of liberalizing of imported grain markets in Korea has been progressing relatively well. This is important for Korean grain importers and livestock producers who rely heavily on international price signals.
Keywords: Price Transmission; Causality; Korean grain prices; U.S. grain prices.; Price Transmission; Causality; Korean grain prices; U.S. grain prices.